Huge Nulliparous Prolapse with Cervical Dystocia - Seth, Shikha; Singh, Dinesh K; Deoghary, Rajni (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i2.5081 NJOG 2010 Nov-Dec; 5(2): 50-51